FACTORS CONTRIBUTING TO ABSENTEEISM AMONG STUDENTS OF GOMAL MEDICAL COLLEGE - Adnan Khan; Israr Ul Haq; Danish Zafar; Nargis Noman; Saima Bashir; Samia Iftikhar (Journal of Ayub Medical College Abbottabad, 2024)
Background: Absenteeism in educational settings is a significant barrier to academic success and skill development. This study investigates the socio-demographic factors contributing to absenteeism among students at Gomal Medical College MTI, Dera Ismail Khan, KPK, highlighting the importance of class attendance for fostering essential job-related skills and overall student development. Methods: Utilizing a cross-sectional study design, this research was conducted from April to September 2023 within the Community Medicine Department of Gomal Medical College. The study population included students from 1st to final year, using a non-probability convenience sampling method. According to Raosoft Sample size calculator for population of 566 total students with confidence interval of 95%, margin error 5% and response rate 50%, the sample size was determined to be 230. Results: Among the participants, 42.4% were female and 57.6% were male, with 76.4% residing in hostels. Key factors leading to absenteeism included the perception of being able to pass exams without attending lectures, disrupted sleep patterns, and the need to prepare for other exams. College-related factors such as non-interactive classes and a communication gap with teachers were also significant. Conclusion: Absenteeism is influenced by both student-centric and institutional factors, with a prevalent belief among students that physical attendance is not essential for academic achievement.